Strategi Komunikasi Customer Loan Service Dalam Pelayanan Kredit Nasabah pada PT. Bank Tabungan Negara (Persero) Tbk Kc. Medan - Lily Nur Indahsari; Zainarti Zainarti (Universitas Labuhanbatu, 2022)
Communication strategy is an important element in a communication process, including in customer credit services by customer loan services at PT. Bank Tabungan Negara (Persero) TBK KC Medan. This is a fundamental element in order to achieve effective communication in the credit service process for customers. The study used a qualitative approach with a qualitative descriptive method. The data were collected through observation, interviews, and document studies. The results of this study indicate that the communication strategy is very important and is always considered in the service of the customer loan service at PT. Bank Tabungan Negara (Persero) TBK KC Medan. The communication strategy applied is aimed at achieving communication effectiveness. The stages of the communication strategy are carried out through four stages, namely the stage of knowing the audience, determining the message, determining the method, and selecting and selecting media. All these stages are carried out by the customer loan service staff of Bank BTN KC Medan in order to achieve maximum communication and service effectiveness for customers.